Pengaruh Kepemimpinan Transformasional, Transactional dan Authoritarian Terhadap Komitmen Organisasi (Studi kasus Pada Organisasi Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Karmilaturrahman, Karmilaturrahman; Wahono, Budi; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine the influence of Transformational, Transactional and Authoritarian Leadershiptowards organizational commitment. Type of quantitative survey research approach. The population in this study were members of organizations at the economics and business faculty of the Islamic University of Malang. The sampling technique uses purposive sampling with a sample of 77 respondents. Data was obtained from a questionnaire using Likert scale. Analysis of this research data uses multiple linear regression analysis. This research contributesto find out the factors that influence Organizational Commitment. Result of This research shows that Transformational and Transactional leadership have a positive and significant effect on organizational commitment, while Authoritarian Leadership does not have a significant effect on organizational commitment..  Keywords: Organizational Commitment, Transformational, Transactional and Authoritarian